THE APPLICATION OF SOCIOLOGY OF LITERATURE : A STUDY ON LOE TOLSTOYS THE THREE HERMIT - ., Kustinah (MAGISTRA, 2004)
What is sociology? Why do people ask a sociological question? According to Peter Berger and Brigitte Berger in their book entitled Sociology : A Biographical Approach (1981) such as question is raised because people are suddenly facing a threat which formerly was thought it was really a treat. When a group of people are in a critical situation, theyll start thinking of a sociological question. Disintegration is one of the most critical question to raise when it happens, especially when it took place among Christian community in the middle age. But now, who cares? Sociology has also something to do with a long term change in a society, i.e. when the capitalist system was born, religious reformation by Luther, the growth of individualism; the birth of modern science; the development of the self confidence; the industrial revolution. Sociology of literature means to observe a literary work from the view point of sociology. The literary facts would be considered as mental evidence; at least the description is what the author thinks about the facts he has observed. This study portrays on aspect of sociology throught a literary work. Leo Tolstoy (1828-1910), the great Russian novelist wrote a short story entitled The Three Hermits. Generally known, Russian is a socialist country, with comunist parties; but as himself was a radical and pacifist Chistianty; this short story perfoms a different colour of a socialist community. Tolstoy put a spirit of Christianty along the story. From sociological point of view, literature is in some wyas a portrayal of society. It is because literature present thoughts and dreams of the characters, literature becomes an alternative of realy that we can see, hear, smell, touch and taste. Literature is a picture of what people think of the constitution, sociology is an attempt to make sense of ways in which we live our lives. This suggests that sociology has it self represented a critical discipline (Burns and burns, 1973 : 9).